Hubungan Tingkat Pendidikan dan Status Pekerjaan Ibu dengan Pengetahuan Ibu tentang Anemia pada Anak Balita di Kelurahan Nambangan Kidul Kecamatan Manguharjo Kota Madiun - Rahmawati, Septiana, Endang Nur W, S.St., M.Si.Med, Luluk Ria Rakhma, S.Gz., M.Gizi (2015)
NUTRITION PROGRAM FACULTY OF HEALTH SCIENCE MUHAMMADIYAH UNIVERSITY OF SURAKARTA RESEARCH PAPER ABSTRACT SEPTIANA RAHMAWATI. J310 121 008 THE CORRELATION OF MOTHERS' EDUCATION DEGREE AND OCCUPATION STATUS WITH MOTHERS' ANEMIA KNOWLEDGE TO CHILDREN UNDER-FIVE IN KELURAHAN NAMBANGAN KIDUL KECAMATAN MANGUNHARJO MADIUN CITY Introduction:The result of introduction survey, there are 15, 6% children under-five are malnutrition in Kelurahan Nambangan Kidul and as much as 35, 3% from 17 children under-five anemia. Social-economic factors can also influence it, like: education, dietary habit, health facilities, and culture factors. The result of the research indicated parents' occupation and education are very influential for anemia case at children under-five. The objective:Know the relationship of mothers' education degree and occupation status with mothers' anemia knowledge to children under-five in Kelurahan Nambangan Kidul Kecamatan Mangunharjo Madiun city. Research method: the type of research is observational using crossectional design. The total samples are 85 participants. The collecting data is participants' characteristic including mothers' name, last education, job, the number of family members, the average family income, knowledge data and the location image of research data. The research used chi square test to know the correlation of mothers' education degree and occupation status with mothers' anemia knowledge to children under-five The result:68, 2% the participants of higher education degree, 65, 9% mothers' occupation status, who do not work, and 56, 5% the good participants' anemia knowledge. 44, 71% the participant of higher education degree, who are good anemia knowledge.34, 12% the participants who do not work at occupation status and less anemia knowledge. There is meaningful correlation between mothers' education and mothers' anemia knowledge (x=6,079, p=0,014<0,05). There is meaningful correlation between mothers' occupation status and mothers' anemia knowledge (x=4,552, p=0,033<0,05). Conclusion: There is correlation between education degree and mothers' anemia knowledge, and there is relationship between occupation status and mothers' anemia knowledge. Key word:Education degree, occupation status, anemia knowledge. Bibliography: 43 : 2000 - 2013